Jury review - Ibrahim, Faridah Hanum; Ho, Desmond; Ismail, Rose; Tengku Muda Mohamed, Mahmud (University Putra Malaysia, 2012)

(untitled)
This project is about fruits that are found in Malaysia and outsidethe country. Fruits are commonly perceived as edible and fit for human consumption. This exhibition shows that fruits are more than just this simple notion. It reveals not only the simplicity of looks alone but also the science behind it together with complexity inherent within many species of fruits. There are more than just the Latin names of fruits that falls within the science of taxonomy. There are genetic materials which are coded and passed down from generations which got entangled with evolutionary processes and hence altering them to become new species and varieties. Some fruits are also associated with insects for pollination and thus some peculiar looking fruits like the figs exist in nature.